Calculate Force

F = -K x (X - X_{0})

F = Force K = Spring Constant X = Distance from Equilibrium X_{0} = Spring Equilibrium Position

Calculate Spring Constant

K = Spring Constant F = Force X = Distance from Equilibrium X_{0} = Spring Equilibrium Position

Calculate Distance from Equilibrium

X = Distance from Equilibrium X_{0} = Spring Equilibrium Position K = Spring Constant F = Force

Calculate Spring Equilibrium Position

X_{0} = Spring Equilibrium Position X = Distance from Equilibrium K = Spring Constant F = Force